Utility of the Merchant View Radiograph for Assessment of Tibial Tubercle-Trochlear Groove Distance: A Comparison to MRI in Pediatric and Adolescent Patients. Issue 8 (8th September 2021) - Bernholt, David L.; Lamplot, Joseph D.; Block, Andrew M.; Nepple, Jeffrey J.
Abstract : Background: Plain radiographic evaluation remains the standard initial assessment of patellar instability, while 3-dimensional imaging is obtained in some patients. Merchant radiographs can demonstrate the tibial tubercle relative to the trochlear groove (TT-TG), but the determination of the TT-TG from these radiographs has been abandoned since its original description. The purpose of this study is to evaluate the utility of the TT-TG measured on Merchant radiographs for the assessment of patellar instability. Methods: A prospective cohort study was performed of pediatric and adolescent patients aged 10 to 18 who underwent standardized Merchant radiographs, including a total of 98 knees (in 57 patients). Merchant TT-TG was measured as the distance between the center of the trochlear groove and the tibial tubercle, with both lines perpendicular to the anterior femoral condylar axis. In Part 1, the Merchant TT-TG measured by the tibial tubercle radiographic appearance was compared with the measurement utilizing a radiographic marker. In Part 2, the Merchant TT-TG was compared with the magnetic resonance imaging (MRI) TT-TG distance using bivariate linear regression analysis. TT-TG measurements were compared in patients with and without patellar instability with receiver operating characteristic curve analysis. Results: The tibial tubercle was identified on Merchant radiograph in 81.7% (67/82) of knees, and there was an excellent correlation (Pearson correlation coefficient=0.85) between the Merchant TT-TG and the measurement based on marker placement. Merchant TT-TG was on average 4.5 mm less than MRI TT-TG (12.8±4.4 vs. 8.4±7.7 mm, P <0.001) and was moderately correlated (Pearson correlation coefficient=0.58, P <0.01). TT-TG distance was increased in patients with patellar instability compared with those without patellar instability on the Merchant view (10.5±6.9 vs. 2.0±5.5 mm, P <0.001) and MRI (13.9±4.4 vs. 10.5±2.9 mm, P =0.012). Merchant TT-TG also demonstrated a higher area under the curve than MRI TT-TG (0.872 vs. 0.775) in differentiating patients with and without patellar instability. Conclusions: Standardized Merchant radiographs allow for reliable assessment of the Merchant TT-TG distance when the tibial tubercle is visualized and moderately correlate with MRI TT-TG (with Merchant TT-TG on average 4.5 mm less than MRI). Level of Evidence: Level III.